Implementation of Town and School Watching for Disaster Education to the Communities in Sidomulyo Village, Pronojiwo, Lumajang - Maryanto, Sukir; Setyowati, Alvira Galihputri; Aprilla, Arga Nanda; Sari, Rendi Pradila Hab; Ramadhani, Naufal Helmi; Tolle, Herman; Nurjannah, Nurjannah; Sujarwo, Sujarwo; Harmoko, Udi (TDMRC, Universitas Syiah Kuala, 2022)
The eruption of Mount Semeru on December 4, 2021, caused a fairly high death toll of up to 50 people. The high number of fatalities is caused by the lack of mitigation capacity and the absence of community involvement in mitigation efforts. Increased mitigation capacity can be done by presenting disaster education to the communities. Thus, we applied the concepts of school watching and town watching in Pronojiwo District, Lumajang Regency. School watching was implemented in eight schools located at Sidomulyo Village. We also carried out town watching in Sidomulyo Village and brought out 33 residents to the Sidomulyo village hall. The implementation of school watching and town watching in Pronojiwo District can increase community involvement in disaster mitigation efforts and public awareness of mitigation efforts.